2010
DOI: 10.1111/j.1465-7295.2010.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Talent and/or Popularity: What Does It Take to Be a Superstar?

Abstract: We show that both talent and popularity significantly contribute to stars' market values in German soccer. The talent-versus-popularity controversy on the sources of stardom goes back to Rosen (1981) and Adler (1985). All attempts to resolve the controversy empirically face the difficulty of accurately identifying talent. In professional sports, rank-order tournaments help in ascertaining talent. Analyzing a team setting, we use 20 different performance indicators to estimate a player's talent according to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 43 publications
(68 reference statements)
4
134
0
3
Order By: Relevance
“…4 Alternatively, we could use salary data to proxy talent. However, we refused this approach as both a player's talent and his popularity influence salaries in German soccer (Franck & Nüesch, 2007). 5 We are grateful to an anonymous referee for raising this issue.…”
Section: Estimation Of a Player's Talentmentioning
confidence: 92%
See 2 more Smart Citations
“…4 Alternatively, we could use salary data to proxy talent. However, we refused this approach as both a player's talent and his popularity influence salaries in German soccer (Franck & Nüesch, 2007). 5 We are grateful to an anonymous referee for raising this issue.…”
Section: Estimation Of a Player's Talentmentioning
confidence: 92%
“…8 Other performance statistics -like flick success rate, tackling success rate, shots off target, shots hitting the woodwork, blocked shots, fouls, hands, balls caught by the goalkeeper, or balls dropped by the goalkeeper -do not significantly affect the team's winning probability. For further information about the team production estimates, see Franck and Nüesch (2007). 9 Summary statistics revealed that goalkeepers received higher average performance statistics than defenders, midfielders, or attackers, even though various studies show that they receive the lowest salaries on average (e.g.…”
Section: Estimation Of a Player's Talentmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, that data is not available for most of the years we include in our analysis. In another study Franck and Nüesch (2007) use as a proxy for individual salaries-as opposed to team wage bills-the individual players' market values as published by www.transfermarkt.de and by Kicker soccer magazine. That data too is available only for a rather short sub-period of our investigation (since the beginning of the 1995/1996 season).…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that multiple mediocre performances do not add up to the quality found in one great performance (Rosen 1981) magnifies the importance of finding these superstars. Hamlen (1991Hamlen ( , 1994 and Kruger (2005) analyze this in vocal musical talent and Franck and Nüesch (2010) analyze both talent and popularity in German soccer to see what it takes to be a superstar. Our data provide a unique opportunity to study the value of both performance and celebrity on superstar status by analyzing NASCAR drivers.…”
Section: The Value Of Superstars In Corporate Sponsorshipmentioning
confidence: 99%